Overview of Anti Streptolysin O Test Results in Postpartum Fever Mothers in the Ciamis Region - Ary Nurmalasari; Rohaidah Rohaidah; Doni Setiawan (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: Puerperal fever is a symptom of postpartum infection. Symptoms of fever during puerperium often occur due to infection with group A Streptococcus hemoliticus bacteria. Objective: The purpose of this study was to determine the description of the results of anti-streptolysin o examination in mothers for the diagnosis of fever in the puerperium. Method: This study is a descriptive study conducted from January to May 2023 with 40 respondents who were in the postpartum period in the Ciamis Health Center working area. The instrument used was the slide method ASTO examination. The data collection technique was based on Accidental sampling which was then processed and presented descriptively in tabular form and explained in narrative. Result: The results of the Anti Streptolysin O examination of 40 respondents showed positive results as many as 2 people (5%) and 38 people (95%) with negative results. Conclusion: It can be concluded that mothers who are in the postpartum period in the Ciamis Health Center working area have negative Anti Streptolysin O average results.